Desarda repair versus other inguinal hernia repairs: a review of global data of 35578 patients - Desarda, Mohan P. (International Surgery Journal, 2022)
The aim of the present review study was to compare the outcomes of non-mesh Desarda technique with open mesh, Bassini and Lap repairs for inguinal hernia over a period of last 20 years. An internet search for RCTs/comparative studies comparing outcomes between Desarda and other repairs like open mesh, Bassini and Lap repairs were done. Search for individual studies was also conducted. RCT/comparative studies and individual non comparative studies comprising 35578 patients were found in search. All those published articles were downloaded from the internet. Some articles were directly obtained from the authors. Outcomes of these articles were evaluated and compared for recurrence, chronic pain, complications, free mobility, return to normal work and cost. A total number of 80 RCTs/comparative studies and 53 individual studies were included in this review with total number of 35578 patients. Recurrence 0.87% versus 5.6%, chronic pain 1.8% versus 22.5%, complications 6.87% versus 20.6%, free mobility 37.6 hours versus 77.2 hours, return to normal work 10.2 days versus 16.7 days and cost $40.8 versus $68.5 was seen in Desarda versus other repairs, respectively. Desarda repair showed much superior results over other repairs like open mesh, Bassini or Lap repairs in terms of recurrence, chronic pain, complications, free mobility, return to normal work and the cost.